Uso do fogo em propriedades rurais do cerrado em Cavalcante, GO - Daniel Xavier Lara; Nilton César Fiedler; Marcelo Brilhante de Medeiros (Ciência Florestal, 2007)
The use of fire as a land tool management is a common practice in the agricultural area. This practice requires a lot of care to avoid forest fires and uncontrollable fires. The uncontrollable fires can reach plantations, pastures and improvements. The objective of this work was to evaluate the fire management patterns and economic impacts of the fire management in the country areas in the region of Chapada dos Veadeiros, in the city of Cavalcante, Goiás. The data collection was made by means of direct interviews, burnt areas, improvements damages and costs evaluation. Fifty agricultural producers used the fire as a tool of farming handling. The first stage of the data collection was carried out during 2003. Information on the size of burnt area, damages and investments in wildfire prevention was collected. The second survey, mode with the same 50 land owners, was carried out in 2004 dry station. The data of 2003 and 2004 was compared. Results showed that the use of fire, in such a place, causes damages for those land owners who use the fire as a land management tool and for land owners who do not use it. The lack of prevention activities and fire control approaches are the main causes of uncrontrolled burnts in Chapada dos Veadeiros.